(untitled) (Bangladesh Journal of Zoology, 2021)
A study on diversity, status, and habitat preference of avifauna was conducted from November 2017 to October 2018 in Magura Sadar upazila, Magura. Data was collected through direct field observations using line-transect method. Field surveys were made for three days per month in both rural and urban sites. A total of 140 species of birds belonged to 18 orders and 48 families were reported. Among the total species, 55% (77 species) were non-passerines and 45% (63 species) passerines with the highest individuals were counted under order Passeriformes. Resident bird species were dominant (106 species, 75.71%) over migratory (34 species, 24.28%) species. Species richness was the highest in the rural areas (124 species, 88.57%) and occurrence was the highest in winter season (97 species, 69.29%). The maximum species were recorded from trees (87 species, 62.14%) as preferred habitat. In this study, in total 4,060 individuals of birds were counted and among them, 51.55% (n=2093) were observed in the rural areas and 48.45% (n=1967) were in the urban areas. The highest number of birds was found in December (10.34%, n=432) and seasonal abundance was the highest in winter (40.15%, n=1630). Abundance was the highest for Common Myna (5.76%, n=234) among all recorded species. Diversity indices showed that the bird species were the most diverse in the rural areas in the winter season and in July. Habitat diversity indices were the highest for trees and birds used different types of habitats at different times for roosting, breeding and feeding. Regarding the observation status, 29.28% species was very common, 4.28% common, 31.42% fairly common, and 35% were few. This baseline data indicate that this study site is significant from the ecological and conservation point of views. Therefore, further research is necessary to understand how this avian diversity is maintained in this ecological setting. Bangladesh J. Zool. 48(2): 441-456, 2020